Does use of an antiarrhythmic drug prior to cryoballoon pulmonary vein isolation impact the duration of the post-ablation blanking period?. (14th October 2021) - Saberito, M; Milstein, N; Bhatt, A; Habibi, M; Sichrovsky, T; Preminger, M; Shaw, R; Mittal, S; Musat, D
Abstract: Background: At time of cryoballoon (CB) pulmonary vein isolation (PVI), some patients with atrial fibrillation (AF) are on an antiarrhythmic drug (AAD) while others are not. The impact of AAD use at time of CB PVI on the duration of post-ablation blanking period (BP) is unknown. Objective: To determine whether the optimal BP duration differs between pts who were and were not taking an AAD at time of CB PVI. Methods: We enrolled consecutive pts with AF who had initial CB PVI; all pts had an implantable loop recorder (ILR). We prospectively followed all pts and determined the time to last AF episode during the 90-day post-PVI BP. This was then correlated with likelihood of having an AF recurrence between 3–12 months post-PVI. Results: The cohort included 165 pts (66±9 years; 99 [60%] male; 91 [55%] PAF; CHA2DS2-VASc 2.7±1.6). An AAD was being used at some point prior to ablation in 120 (73%) pts. An AAD was being used at time of CB PVI in 92 (77%) of these 120 pts; this was stopped at a median of 80 [36, 105] days post-PVI. We defined 4 distinct groups: (1) no AF in 90-day BP (n=75 [45%]); (2) last AF within 30 days of PVI (n=32 [19%]); (3) last AF within 60 days of PVI (n=17 [10%]); and (4) last AF within 90 days of PVI (n=41 [25%]). Patients not exposed to an AAD prior to CB PVI had significantly lower likelihood of having no AF in the first 90-days post ablation (p=0.004, Figure). In contrast, if AF was observed post-ablation, as time from ablation to recurrence increased, so did likelihood of long-term failure from ablation (Figure); this relationship was not impacted by use of an AAD. Conclusion: The best long-term outcomes post CB PVI are seen in pts who had no prior exposure to an AAD and had no AF within the first 90 days of ablation. Subsequently, as the time from ablation to AF recurrence increased within the 90-day BP, so did likelihood of recurrent AF during long-term follow-up, irrespective of whether an AAD was or was not used. Funding Acknowledgement: Type of funding sources: None.